Scattering of gap solitons by PT-symmetric defects - Abdullaev, Fatkhulla; Brazhnyi, V. A.; Salerno, M. (2014)
The resonant scattering of gap solitons of the periodic NLS equation with a PT-symmetric defect is investigated. For suitable parameters of the defect potential the resonant transmission of soliton through the defect becomes possible.